Hidrogéis magneto-reponsivos para liberação estimulada de fármacos - Bortolin, Adriel (2018)
Nanocomposite hydrogels modified with polysaccharides, minerals clay and magnetic nanoparticles of iron oxide functionalized with polymeric material were developed, allowing higher interaction between the nanoparticles and the hydrogel matrix. The nanocomposites were synthesized with small amounts of magnetic nanoparticles (0.5 - 2.0% w/w) and in all proportions magnetic properties were observed, as visibly by interaction with a magnet and experimentally through VSM analysis. The materials were subjected to several characterizations applying constant magnetic field of 0.23 Tesla. The magnetic field influenced directly all the properties of the nanocomposite materials, increasing the rate of water absorption and release of the active principle present in the structure (streptomycin), up to 5 times faster than the active material without application of magnetic field. Release tests on bacterial cultures also showed the bactericidal efficiency of the hydrogels loaded with streptomycin, where with the application of the magnetic field there was an average increase of 16.4 % in the inhibition radius of the bacteria studied. The release mechanism for hydrogels follows a pseudo-2nd order model, indicating the interaction between the active and specific sites of the hydrogel, and rearrangements may occur in the release mechanism. Magnetic hydrogels presented a pulsatile release behavior with the application of the field whose intensity was directly related to the concentration of nanoparticles used in the synthesis of hydrogels. Thus, the obtained hydrogels present characteristics that make possible the application in responsive systems of drugs release.